Sixties Rock: Garage, Psychedelic, and Other Satisfactions - Berger, Harris M. (Labour / Le Travail, 1999)
The article reviews the book, "Sixties Rock: Garage, Psychedelic, and Other Satisfactions," by Michael Hicks.